Law Enforcement In Responding To Social Media User's Provocation That Results In Competitive Fights - Randy Krisna Putra Mandelly; Tanudjaya; Nynda Fatmawati Octarina (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
This study aims to determine the role of law in Indonesia in tackling cases with provocation types on social media. Like the provocation that occurs on social media, it triggers a fight. In this study, the authors review the negative side of social media in throwing provocations which result in duels, because duels are fights in physical or verbal contact involving 2 (two) different individuals to duel to resolve problems between the two. In conducting research, the author uses a normative juridical approach using laws and regulations as study material. With reference to Law no. 19 of 2016 and Articles 182 – 183 of the Criminal Code are expected to be able to answer questions regarding problematic. The purpose of this study is to reinforce the rule of law in social media provocations which are expected not to recur, This research is a normative juridical research method that originates from written regulations in the form of statutory regulations in the positive law applicable in Indonesia. As well as the authors use descriptive research, where the authors will provide studies and an overview of law enforcement in social media and implementation in the real world by measuring the policy of imposing criminal penalties against perpetrators of duel fights.